2017
DOI: 10.1016/j.chom.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

A Bacterial Type III Effector Targets the Master Regulator of Salicylic Acid Signaling, NPR1, to Subvert Plant Immunity

Abstract: Most plant bacterial pathogens rely on type III effectors to cause diseases. Although it is well known that the plant hormone salicylic acid (SA) plays an essential role in defense, whether the master regulator of SA signaling, NPR1, is targeted by any plant pathogen effectors is unknown. SA facilitates the reduction of cytosolic NPR1 oligomers into monomers, which enter the nucleus and function as transcriptional coactivators of plant defense genes. We show that SA promotes the interaction between the Pseudom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 57 publications
4
94
0
1
Order By: Relevance
“…Remarkably, a recent study reported that the effector AvrPtoB could ubiquitinate and mediate the degradation of NON‐EXPRESSER OF PR GENES 1 (NPR1), a master regulator of salicylic acid (SA) signaling and plays an essential role in ETI, to block SA‐dependent immunity (Cao et al 1997; Chen et al 2017). A more recent study also demonstrated that the effector HopBF1 from P. syringae mimics as a client of HEAT SHOCK PROTEIN 90 (HSP90), which facilitates the maturation and activation of multiple NLRs, to specifically interact with and phosphorylate HSP90, resulting in the inactivation of HSP90 and suppression of NLRs‐mediated immunity (Schulze‐Lefert 2004; Kadota and Shirasu 2012; Lopez et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, a recent study reported that the effector AvrPtoB could ubiquitinate and mediate the degradation of NON‐EXPRESSER OF PR GENES 1 (NPR1), a master regulator of salicylic acid (SA) signaling and plays an essential role in ETI, to block SA‐dependent immunity (Cao et al 1997; Chen et al 2017). A more recent study also demonstrated that the effector HopBF1 from P. syringae mimics as a client of HEAT SHOCK PROTEIN 90 (HSP90), which facilitates the maturation and activation of multiple NLRs, to specifically interact with and phosphorylate HSP90, resulting in the inactivation of HSP90 and suppression of NLRs‐mediated immunity (Schulze‐Lefert 2004; Kadota and Shirasu 2012; Lopez et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, how pathogen effectors target NPR1 to diminish SA-dependent signaling pathway remained a mystery until recently. An impressive recent research reported that the P. syringae type III effector AvrPtoB, a U-box type E3 ubiquitin ligase, mediates the degradation of NPR1 via host 26S proteasome, resulting in disrupting SA signaling, pattern-triggered immunity and systemic acquired resistance (Chen et al 2017). In addition, a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The SUMO-interaction motif (SIM3) located in the ANK domain of NPR1 is modified by SUMO3 to regulate the defence response 36 . Pseudomonas syringae type III effector AvrPtoB targets NPR1 and subverts plant innate immunity by repressing NPR1-dependent SA signalling 37 . ACD6 and BDA1 are also ANK proteins and function as positive regulators of SA signalling in defence responses [38][39][40] .…”
Section: Discussionmentioning
confidence: 99%